Practicing the law of human dignity - Chatzipanagiotou, Matthildi (My University, 2014)
The philosophical underpinnings of what may be called the meta-dimension of the law of human dignity trigger a question that surpasses the boundaries of the discipline of law: how could the transcendental as an aspect of human dignity meaning be portrayed? The insistence on non-determination of the Menschenbild [human image] or ‘God’ in the Preamble to the German Basic Law [Grundgesetz] reflected in German legal doctrine, paired with the commitment to case-by-case ad hoc concretization of what human dignity means inspire this story of ‘something missing’. In postmodern fashion, this story portrays the law of human dignity as a Trojan Horse and provides hermeneutic and literary foundations for an affirmative stance towards ‘emptiness’ talk in legal discourse. The research question rekindles and twists polemically framed ‘emptiness’ and ‘black box’ contentions: Why does the legal concept of human dignity appear ‘empty’? Or, how is it ‘empty’? Why and how is it a ‘black box’? How do manifestations of the concept appear abstract as universals and concrete as particulars? The ontological, linguistic-analytical, and phenomenological philosophical insights presented in Chapter One compose the lens through which five benchmark Bundesverfassungsgericht cases – on abortion, life imprisonment, transsexuals, state response to terrorist attacks, and the guarantee of a dignified subsistence minimum – are analyzed in Chapter Two. The philosophical sources are not bracketed as moments in the long course of human dignity in the history of ideas.

Die philosophischen Grundlagen der Meta-Dimension des Rechts auf Menschenwürde lösen eine Fragestellung aus, die die Grenzen der Disziplin des Rechts übertrifft: wie könnte das Transzendentale als ein Aspekt der Bedeutung von Menschenwürde dargestellt werden? Das Beharren auf der nicht-Bestimmung des Menschenbildes oder auf dem Begriff ‚Gott’ in der Präambel des Deutschen Grundgesetzes, wie es sich in der Deutschen Dogmatik widerspiegelt, gepaart mit dem Bestreben nach einer Fall-zu-Fall ad hoc Konkretisierung dessen, was Menschenwürde bedeutet, inspiriert diese Untersuchung von ‚etwas fehlt’ [‘something missing’]. In postmoderner Art und Weise beschreibt diese Geschichte das Gesetz der Menschenwürde als Trojanisches Pferd und bietet hermeneutische und literarische Grundlagen für eine affirmative Haltung gegenüber einer ''leeren'' Rede im juristischen Diskurs. Die Forschungsfrage erweckt und umkreist die polemisch verbrämten Begriffe von ‚Leere’ und ‚Black Box’: Warum erscheint der Rechtsbegriff der Menschenwürde ‚leer’? Oder wie ist er ‚leer’? Warum und wie ist er eine ‚Black Box’? Wie erscheinen Manifestationen des Konzepts abstrakt wie Universalien, aber im Einzelnen konkret? Die ontologischen, sprachlich-analytischen und phänomenologischen philosophischen Erkenntnisse, vorgestellt im ersten Kapitel, bilden die Linse, durch die fünf maßgebliche Fälle des Bundesverfassungsgerichtes – über Abtreibung, lebenslange Freiheitsstrafe, Transsexualität, staatliche Reaktion auf Terroranschläge und die Gewährleistung eines menschenwürdigen Existenzminimums – im zweiten Kapitel analysiert werden. Die philosophischen Quellen werden nicht als Momente im langen Verlauf der Menschenwürde in der Geschichte der Ideen eingeklammert.
A story of 'something missing'
Keywords: Recht; Religion; Sprache; Abtreibungsdebatte; Abtreibungsgegner; Abtreibungsverbot; Transsexualität; Transdisziplinarität; Menschenbild; Haft; Lohn; 340 Recht; Menschenwürde